Intercultural communication competence in a global virtual team - Paukku, Jaakko (My University, 2022)
Abstract In recent years, the global prevalence of remote work has rapidly increased. This has been caused by the COVID-19 pandemic, as well as the effects of globalisation. A specific form of remote work is a global virtual team (GVT). A GVT refers to a team that uses computer-mediated technology to communicate in order to work towards a common goal, and is temporary, multicultural, and geographically dispersed. The communication in such a team also involves interactions among people of different cultures, intercultural communication. This can be characterised by misunderstandings and communication failures. However, intercultural communication competence (ICC) can aid in achieving mutual understanding. ICC refers to the ability to effectively and appropriately interact with people of different cultural backgrounds. The purpose of this study is to answer the research question: How can intercultural communication competence be applied in a global virtual team? Answering to the question involves descriptions and categorisations of intercultural communication and collaboration challenges, and of solutions to the challenges in the form of ways of applying ICC. The research design of this study included an expert interview, and a single case study of a GVT. The GVT consisted of students at multiple universities. The interview findings indicated that making assumptions related to culturally different others based on insufficient information was the basis of all intercultural communication challenges in a GVT. One solution to this challenge was extending the time of analysing one another’s communication. The case study findings indicated that the most pronounced and common challenges faced by the GVT were related to coordination, particularly to some members’ lack of commitment, which led to other challenges. One solution to the challenge was starting an interaction in order to involve team members in collaboration. Many of the challenges can be related to one another. Furthermore, solutions in the form of ways of applying ICC can be devised, if not to all, at least to nearly all communication and collaboration challenges faced in a GVT. Knowledge of these challenges and ways may allow companies and their employees to overcome and prevent such challenges, improve their intercultural communication and collaboration, as well as ultimately experience increases in task and relationship outcomes.

Tiivistelmä Viime vuosina etätyö on nopeasti yleistynyt maailmanlaajuisesti. Syinä tähän ovat olleet COVID-19-pandemia sekä globalisaation vaikutukset. Etätyön erityinen muoto on globaali virtuaalitiimi (GVT). GVT viittaa tiimiin, joka viestii tietotekniikan välityksellä työskennelläkseen yhteisen tavoitteen hyväksi, ja on väliaikainen, monikulttuurinen, ja maantieteellisesti hajautunut. Tällaiseen viestintään kuuluu eri kulttuurien edustajien välistä vuorovaikuttamista, kulttuurienvälistä viestintää. Tähän voi liittyä väärinymmärryksiä ja viestinnän epäonnistumisia. Kuitenkin, kulttuurienvälinen viestintäkompetenssi (KVK) voi auttaa molemminpuolisen ymmärryksen saavuttamisessa. KVK viittaa kykyyn viestiä tehokkaasti ja soveliaasti eri kulttuuritaustaisten ihmisten kanssa. Tämän tutkimuksen tarkoituksena on vastata tutkimuskysymykseen: Miten kulttuurienvälistä viestintäkompetenssia voidaan soveltaa globaalissa virtuaalitiimissä? Tähän kysymykseen vastaamiseen liittyy kulttuurienvälisen viestinnän ja yhteistyön haasteiden, ja näiden ratkaisujen kuvailuja ja luokitteluja. Ratkaisut viittaavat tapoihin soveltaa KVK:ta näihin haasteisiin. Tämän tutkimuksen tutkimusasetelmaan sisältyi asiantuntijahaastattelu, ja yksittäistapaustutkimus GVT:stä. Haastattelulöydökset viittasivat siihen, että oletusten tekeminen liittyen kulttuurisesti erilaisiin toisiin perustuen riittämättömään informaatioon oli kaikkien kulttuurienvälisten haasteiden perusta GVT:ssä. Yksi ratkaisu tähän haasteeseen oli osapuolten toistensa viestinnän analysointiajan pidentäminen. Tapaustutkimuslöydökset viittasivat siihen, että korostuneimmat ja yleisimmät haasteet, jotka GVT kohtasi, liittyivät koordinaatioon, erityisesti joidenkin jäsenten sitoutumisen puutteeseen, joka johti muihin haasteisiin. Yksi ratkaisu haasteeseen oli vuorovaikutuksen aloittaminen tiimiläisten osallistamiseksi yhteistyöhön. Monet haasteista voivat liittyä toisiinsa. Lisäksi, ratkaisuja voidaan löytää KVK:n soveltamisen tapojen muodossa, jos ei kaikkiin, ainakin lähes kaikkiin GVT:ssä kohdattujen viestinnän ja yhteistyön haasteisiin. Tieto näistä haasteista ja tavoista voi mahdollistaa yritysten ja näiden työntekijöiden selviytyä näistä haasteista ja ehkäistä näitä haasteita, edistää heidän kulttuurienvälistä viestintäänsä ja yhteistyötänsä, sekä lopulta parantaa tehtävätuloksia ja ihmissuhteita.
Keywords: intercultural communication, competence, virtuality, teamwork, challenges, kulttuurienvälinen viestintä, kompetenssi, virtuaalisuus, tiimityö, haasteet (ongelmat)